Policy Framework for Crime Prevention Based on the Modus Operandi of Human Trafficking in Cibadak District Court Decision No. 92/Pid.Sus/2024/PN.CBD - Sherlyn, Sherlyn; Adhari, Ade (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study investigates the increasing prevalence of human trafficking in Indonesia facilitated through social media platforms as a mechanism for recruiting illegal migrant workers, as illustrated by the Cibadak District Court Decision No. 92/Pid.Sus/2024/PN.Cbd. In this case, the defendant, Clara Emilia Yulianti, and her network recruited prospective migrant workers without official authorization by offering high-paying jobs abroad, thereby exposing significant gaps in state oversight and digital protection for prospective migrants. The objective of this study is to analyze the modus operandi of the illegal recruitment scheme in this case and to evaluate existing prevention policies to address the legal loopholes exploited by the perpetrators. Employing normative legal methods alongside legislative, conceptual, and case study approaches, the study finds that the perpetrators used social media to lure victims, collect fees, and engage in unlawful sheltering and deployment activities in violation of Article 2(1) of Law No. 21/2007 in conjunction with Law No. 18/2017. Preventive efforts should prioritize strengthening oversight of online recruitment through enhanced cooperation between the government and digital platforms to enable detection, verification, and removal of illegal recruitment content.